Parental attitude towards child advertising in Chile: the role of the GSE and the urban-rural dichotomy - Uribe B., Rodrigo; Acuña G, María Constanza; Carrasco G., Alejandra; Checura I., Schlomit (Estudios de Administración, 2006)
This article presents the results of a survey of 421 Chilean parents from different socio-economic backgrounds and places of residence (urban and rural). It aimed to examine their attitudes toward children’s advertising. Results show a general negative view about this issue. The main criticisms were the negative effects of advertising in terms of consumerism and bad alimentary habits as well as the deceiving character of the messages. Nevertheless, it is remarkable that those criticisms do not mean that advertising should be banned but regulated. On the other hand, analyzes by subsamples –socioeconomic level and place of residence– showed that only the former variable was relevant in terms of depicting significant differences: parents from poorer background showed a more positive attitude toward advertising.